Financial crises after financial liberalization: Exceptional circumstances or structural weakness? - Christian E. Weller (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
Recent studies have conjectured that there may be a link between financial liberalization and financial instability in emerging economies. Most of these studies, however, do not investigate whether emerging economies are becoming structurally more vulnerable to currency and banking crises. In this paper, we argue that emerging economies are systematically becoming more susceptible to both currency and banking crises after FL. Using data for 27 emerging economies from 1973 to the present, univariate and multivariate analyses indicate that the likelihood of currency crises and banking crises increase after FL. In particular, liberalization allows more liquidity to enter an emerging economy, which finds its way into productive and speculative projects. What is common to both types of crises is a significant increase in speculative financing, thereby increasing the chance for borrower default. Thus, the outflow of international capital becomes more likely, and we find that the chance of either type of crisis grows faster in response to changes in short-term loans after FL than before. Similarly, the reactions to overvalued currencies are at least similar in terms of increasing probabilities of crises in the case of banking crises, or greater in the case of currency crises after FL as compared to before FL. Further, our results show that after FL the chance of a currency crisis declines over time, while the chance of a banking crisis increases.
Keywords: F02; F36; F43; 330; Emerging economies; Financial liberalization; financial instability; currency crises; banking crises; Kapitalmarktliberalisierung; Schätzung; Währungskrise; Bankenkrise; Devisenspekulation; Aufstrebende Mär